A comparison of continuous video‐EEG monitoring and 30‐minute EEG in an ICU. Issue 4 (December 2014) - Khan, Omar I.; Azevedo, Christina J.; Hartshorn, Alendia L.; Montanye, Justin T.; Gonzalez, Juan C.; Natola, Mark A.; Surgenor, Stephen D.; Morse, Richard P.; Nordgren, Richard E.; Bujarski, Krzysztof A.; Holmes, Gregory L.; Jobst, Barbara C.; et al.
<x xml:space="preserve">Abstract</x> Aim. To determine whether there is added benefit in detecting electrographic abnormalities from 16–24 hours of continuous video‐EEG in adult medical/surgical ICU patients, compared to a 30‐minute EEG. Methods. This was a prospectively enroled non‐randomized study of 130 consecutive ICU patients for whom EEG was requested. For 117 patients, a 30‐minute EEG was requested for altered mental state and/or suspected seizures; 83 patients continued with continuous video‐EEG for 16–24 hours and 34 patients had only the 30‐minute EEG. For 13 patients with prior seizures, continuous video‐EEG was requested and was carried out for 16–24 hours. We gathered EEG data prospectively, and reviewed the medical records retrospectively to assess the impact of continuous video‐EEG. Results. A total of 83 continuous video‐EEG recordings were performed for 16–24 hours beyond 30 minutes of routine EEG. All were slow, and 34% showed epileptiform findings in the first 30 minutes, including 2% with seizures. Over 16–24 hours, 14% developed new or additional epileptiform abnormalities, including 6% with seizures. In 8%, treatment was changed based on continuous video‐EEG. Among the 34 EEGs limited to 30 minutes, almost all were slow and 18% showed epileptiform activity, including 3% with seizures. Among the 13 patients with known seizures, continuous video‐EEG was slow in all and 69% had epileptiform abnormalities in the first 30 minutes, including 31% with seizures. An additional 8% developed epileptiform abnormalities over 16–24 hours. In 46%, treatment was changed based on continuous video‐EEG. Conclusion. This study indicates that if continuous video‐EEG is not available, a 30‐minute EEG in the ICU has a substantial diagnostic yield and will lead to the detection of the majority of epileptiform abnormalities. In a small percentage of patients, continuous video‐EEG will lead to the detection of additional epileptiform abnormalities. In a sub‐population, with a history of seizures prior to the initiation of EEG recording, the benefits of continuous video‐EEG in monitoring seizure activity and influencing treatment may be greater.